CD154 Costimulation Shifts the Local T-Cell Receptor Repertoire Not Only During Thymic Selection but Also During Peripheral T-Dependent Humoral Immune Responses - Fähnrich, Anke; Klein, Sebastian; Sergé, Arnauld; Nyhoegen, Christin; Kombrink, Sabrina; Möller, Steffen; Keller, Karsten; Westermann, Jürgen; Kalies, Kathrin (Frontiers in Immunology, 2018)
CD154 is a transmembrane cytokine expressed transiently on activated CD4 T cells upon T cell receptor stimulation that interacts with CD40 on antigen presenting cells. The signaling via CD154:CD40 is essential for B cell maturation and germinal center formation, but also for the final differentiation of CD4 T cells during T-dependent humoral immune responses. Recent data demonstrate that CD154 is critically involved in the selection of T cell clones during the negative selection process in the thymus. Whether CD154 signaling influences the T cell receptor repertoire during peripheral T-dependent humoral immune responses has not yet been elucidated. To find out, we used CD154 deficient mice and assessed the global T cell receptor β repertoire in T cell zones of spleens by high-throughput sequencing after induction of a Th2 response to the multiepitopic antigen sheep red blood cells. Qualitative and quantitative comparison of the splenic T-cell zone-specific T cell receptor β repertoires revealed that CD154 deficiency shifts the distribution of Vβ-Jβ genes after antigen exposure. This data led to the conclusion that costimulation via CD154:CD40 during the interaction of T cells with CD40 matured B cells contributes to the recruitment of T cell clones into the immune response and thereby shapes the peripheral T cell receptor repertoire.